1967
DOI: 10.1159/000129947
|View full text |Cite
|
Sign up to set email alerts
|

Replication Patterns of the Unpaired Chromosome No. 9 of the Rodent <i>Ellobius lutescens</i> Th.

Abstract: Autoradiographic studies were done of DNA replication in the unpaired chromosome No. 9 of Eilobius lutescens. The replication sequence is identical in both sexes. The unpaired chromosome comprises approximately 5 % of the haploid complement, corresponding to the original-type X chromosome in the majority of placental mammals. The relation of the odd chromosome to the sex-determining mechanism of this species is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
13
0

Year Published

1969
1969
1998
1998

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 1 publication
0
13
0
Order By: Relevance
“…The size of the odd chromosome turned out to be close to 5 %, the size of the "original type" X chromosome of mammals (Ohno et al, 1964). Thus, the single chromosome, definitely, does not represent a fusion product of two X chromosomes (Castro-Sierra and Wolf, 1967). The replication patterns (Fig.…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…The size of the odd chromosome turned out to be close to 5 %, the size of the "original type" X chromosome of mammals (Ohno et al, 1964). Thus, the single chromosome, definitely, does not represent a fusion product of two X chromosomes (Castro-Sierra and Wolf, 1967). The replication patterns (Fig.…”
mentioning
confidence: 86%
“…Detailed studies on the male meiosis of Ellobius lutescens suggested also that the odd chromosome represents a standard type, single mammalian X chromosome (Castro-Sierra and Wolf, 1968). Hence, the original hypothesis by Matthey (1953;1958) and White (1957) was refuted and instead a Y autosome translocation proposed to explain the sex chromosome constitution in this species (Castro-Sierra and Wolf, 1967). The latter hypothesis got additional support from an association between the sex vesicle and an autosomal bivalent in a proportion of cells in male meiosis (Castro-Sierra and Wolf, 1968).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In XO females of M. oregoni and in XV females of M. schisticolor, the XX constitution is restored in oogonia by selective non-disjunction of the X in primordial germ cells (Ohno et al, 1966;Fredga et al, 1976). However, XO females of Mus musculus (Kaufman, 1972), E. lutescens (Castro-Sierra and Wolf, 1968), and D. torquatus (Gileva and Chebotar', 1979b) retain the XO constitution in the germ line, yet females of these species are fertile and phenotypically normal. The reproductive output ofXO Mus, occurring rarely due to sex chromosomal non-disjunction in parental germ cells, is greatly reduced as compared to that of XX dams (Lyon and Hawker, 1973).…”
mentioning
confidence: 99%
“…Yet, while exclusively female progeny is expected in X * Y females, some few females occur that also occasionally produce sons. In a set of data from 115 X * Y females (Frank, unpublished) (Ohno et al, 1963(Ohno et al, , 1966 or in Ello6ius lutescens (Castro-Sierra and Wolf, 1967 ;Nagai and Ohno, 1977). c) Finally, as far as the postulated male-female sex reversal mutation in the wood lemming is concerned, there is at least one comparable condition in man.…”
mentioning
confidence: 99%